The vapB–vapC Operon of Acidovorax citrulli Functions as a Bona-fide Toxin–Antitoxin Module - Shavit, Reut; Lebendiker, Mario; Pasternak, Zohar; Burdman, Saul; Helman, Yael (Frontiers in Microbiology, 2016)
Toxin–antitoxin systems are commonly found on plasmids and chromosomes of bacteria and archaea. These systems appear as biscystronic genes encoding a stable toxin and a labile antitoxin, which protects the cells from the toxin’s activity. Under specific, mostly stressful conditions, the unstable antitoxin is degraded, the toxin becomes active and growth is arrested. Using genome analysis we identified a putative toxin–antitoxin encoding system in the genome of the plant pathogen Acidovorax citrulli. The system is homologous to vapB-vapC systems from other bacterial species. PCR and phylogenetic analyses suggested that this locus is unique to group II strains of A. citrulli. Using biochemical and molecular analyses we show that A. citrulli VapBC module is a bona- fide toxin–antitoxin module in which VapC is a toxin with ribonuclease activity that can be counteracted by its cognate VapB antitoxin. We further show that the transcription of A. citrulli vapBC locus is induced by amino acid starvation, chloramphenicol and during plant infection. Due to the possible role of TA systems in both virulence and dormancy of human pathogenic bacteria, studies of these systems are gaining a lot of attention. Conversely, studies characterizing toxin–antitoxin systems in plant pathogenic bacteria are lacking. The study presented here validates the activity of VapB and VapC proteins in A. citrulli and suggests their involvement in stress response and host-pathogen interactions.